Is the membranous urethral length related to postoperative urinary incontinence after holmium laser enucleation of the prostate?. (24th July 2020) - Ueki, Hideto; Takahashi, Kosuke; Yasufuku, Tomihiko; Yuen, Keiji; Yamashita, Masuo
Abstract : Objectives: To investigate the findings of preoperative magnetic resonance imaging associated with the occurrence of transient urinary incontinence after holmium laser enucleation of the prostate. Methods: At a single institution, 360 patients underwent holmium laser enucleation of the prostate between January 2014 and December 2018. Of those, we retrospectively evaluated 237 who underwent preoperative magnetic resonance imaging and for whom postoperative evaluations were available for >3 months after holmium laser enucleation of the prostate. We carried out preoperative magnetic resonance imaging, and measured the periurethral sphincter complex, levator ani thickness, membranous urethral length and minimal residual membranous urethral length. Logistic regression analysis was carried out to assess the variables associated with incontinence. Results: Transient urinary incontinence occurred after holmium laser enucleation of the prostate in 68 patients (28.7%); 46 (67.6%) of whom recovered within 3 months. Multivariate analysis showed that the membranous urethral length was independently associated with postoperative urinary incontinence at 1 and 3 months after surgery. The operative time was also independently associated with postoperative transient urinary incontinence at 1 month after surgery. Conclusion: Preoperative membranous urethral length and operative time are independent predictors of transient urinary incontinence after holmium laser enucleation of the prostate. These findings should be considered by surgeons before surgery.